SPEECH ACT AND GRICE’S MAXIMS NON OBSERVANCEIN HER WORLD MAGAZINE ADVERTISEMENTS - Riyanti, R Ririn; Sofwan, Ahmad (English Education Journal, 2016)
This research is aimed to analyze the implied meaning inside the elements of advertisement based on Austin’s Speech Act Theory and Non-Observance of Grice’s maxims, and their effects to the readers. The sample of the research are 12 advertisements of ‘her world’ magazine Singapore in edition of December 2013 and 22 participants of the Perlocutionary Act Survey. The analysis results of the advertisements based on Speech Act and Non Observance of Grice’s Maxims were used to arrange survey questionnaires. Surveys for Perlocutionary Act were conducted using sets of questionnaire to seek for reader’s perception towards the advertiser's intentions and the degree of interest of the participants would be in buying the products. The Result Summary of Q1 of the Survey shows that the participant’s recognition towards the Literal Meaning of the advertisement is bigger than that of the Implied Meaning. This is relevant with the result of Q2, the degree of the Participants’ Interest would be in Buying the Products, since Somewhat Interested is the biggest answer. The relationship among Q1 and Q2 explains how perlocutionary act of the advertisements help English ads successfully achieve effect among participants.